UVA-activated 8-methoxypsoralen (PUVA) causes G2/M cell cycle arrest in Karpas 299 T-lymphoma cells - Bartošová, Jitka; Kuželová, Kateřina; Pluskalová, Michaela; Marinov, Iuri; Halada, Petr; Gašová, Zdenka (Journal of photochemistry and photobiology. B, Biology, 2006)
We investigated the effect of UVA-activated 8-methoxypsoralen (PUVA) on the cell line Karpas 299 derived from anaplastic large-cell lymphoma (ALCL) expressing chimeric fusion protein nucleophosmin-anaplastic lymphoma kinase (NPM/ALK). NPM/ALK activates phosphatidylinositol 3 kinase (PI3K)/Akt pathway responsible for the cell protection from apoptosis. We found that PUVA treatment first induced G2/M cell cycle arrest resulting in a decrease in the cell proliferation rate. The mitochondrial apoptosis was triggered immediately following PUVA treatment, as we judged from the unmasking of mitochondrial membrane antigen 7A6. However, the mitochondrial membrane depolarization was not observed and caspase-3 was only slightly activated. The late apoptotic events were lacking: neither translocation of phosphatidylserine to the outer side of plasma membrane nor DNA fragmentation occurred. We revealed that PUVA enhanced the expression of peroxiredoxin, stress protein endoplasmin and galectin-3. Galectin-3 has been shown to protect mitochondrial membrane integrity and prevent cytochrome c release thereby blocking the effector stage of apoptosis. We suggest that the elevated level of this protein following PUVA treatment acts in synergy with the constitutively expressed chimeric kinase NPM/ALK to block the apoptosis.
Keywords: galektin 3; methoxsalen; financování organizované; kaspasa 3; Lymphoma, T-Cell; PUVA Therapy; cytochromy c; buněčné linie; Peroxidases; Phosphatidylinositol 3-Kinases; Mitochondria; PUVA terapie; G2 fáze; Membrane Glycoproteins; Heat-Shock Proteins; Methoxsalen; peroxidasy; Ultraviolet Rays; fosfatidylinositol-3-kinasy; membránové proteiny; Cell Line; lymfom T-buněčný; mitochondrie; peroxiredoxiny; Financing, Organized; Cell Cycle Proteins; Cytochromes c; G2 Phase; Galectin 3; Peroxiredoxins; Membrane Proteins; Caspase 3; membránové glykoproteiny; Protein-Tyrosine Kinases; proteiny buněčného cyklu; proteiny teplotního šoku; tyrosinkinasy; ultrafialové záření